A proteogenomic analysis of the adiposity colorectal cancer relationship identifies GREM1 as a probable mediator - Lee, Matthew; Hatcher, Charlie A.; Hazelwood, Emma; Goudswaard, Lucy J.; Tsilidis, Konstantinos K.; Vincent, Emma E.; Martin, Richard M.; Smith-Byrne, Karl; Brenner, Hermann; Cheng, Iona; Kweon, Sun-Seog; Le Marchand, Loic; et al. (International journal of epidemiology, 2025)
Background: Adiposity is an established risk factor for colorectal cancer (CRC). The pathways underlying this relationship, and specifically the role of circulating proteins, are unclear. Methods: Utilizing two-sample univariable Mendelian randomization (UVMR), multivariable Mendelian randomization (MVMR), and colocalization, based on summary data from large sex-combined and sex-specific genetic studies, we estimated the univariable associations between: (i) body mass index (BMI) and waist–hip ratio (WHR) and overall and site-specific (colon, proximal colon, distal colon, and rectal) CRC risk, (ii) BMI and WHR and circulating proteins, and (iii) adiposity-associated circulating proteins and CRC risk. We used MVMR to investigate the potential mediating role of adiposity- and CRC-related circulating proteins in the adiposity–CRC association. Results: BMI and WHR were positively associated with CRC risk, with similar associations by anatomical tumor site. In total, 6591 adiposity–protein (2628 unique circulating proteins) and 33 protein–CRC (7 unique circulating proteins) associations were identified using UVMR and colocalization. One circulating protein, GREM1, was associated with BMI (only) and CRC outcomes in a manner that was consistent with a potential mediating role in sex-combined and female-specific analyses. In MVMR, adjusting the BMI–CRC association for GREM1, effect estimates were attenuated—suggestive of a potential mediating role—most strongly for the BMI–overall CRC association in women. Conclusion: Results highlight the impact of adiposity on the plasma proteome and of adiposity-associated circulating proteins on the risk of CRC. Supported by evidence from UVMR and colocalization analyses using cis-single-nucleotide polymorphisms, GREM1 was identified as a potential mediator of the BMI–CRC association, particularly in women.